“Interpretación De Los Intereses De Aprendizaje De Los Estudiantes Para Potenciar Las Inteligencias Múltiples En El Proceso De Enseñanza De La Educación Básica Superior De La U.E. Ventanas De La Ciudad De Ventanas, Provincia Los Ríos En El Año 2015”. - Molina Espín, Lidia M. (2015)
Considering that every student has different ways of learning and from that learning students develop multiple intelligences in order to use it in different activities such as in themselves, job, family, etc. This research attempted to determine the incidence of learning interests of multiple intelligences in students of the public and regular high school “Unidad Educativa Ventanas" that is located in Ventanas, Los Rios. This research gave benefits the students directly, encouraged teachers to use strategies for improvement and development of multiple intelligences; This inquiry was descriptive and quantitative. The characteristics and properties of learning interests were identified and characterized in detail based on the literature review, theoretical content, the scientific method and the observation. Additionally, in order to get inherent information to the context of research and respond to the verification of the hypothesis, surveys to students and teachers of basic superior education and an interview to the institutional authority were applied.